2008
DOI: 10.1007/s11832-008-0104-2
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent patellofemoral pain: Implicating the medial patellofemoral ligament as the main pain generator

Abstract: The prototypical patient had anterior/anteromedial knee pain of insidious onset during running and jumping. The most consistent physical findings were focal tenderness at the MPFL, positive terminal J-sign, and an elevated Q-angle. Most patients required only nonsurgical treatments, but 18% underwent surgical interventions for persistent pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Further, the majority of studies evaluating the epidemiology or risk factors for PFP in this population include pubescent, post-pubescent, and even pre-pubescent individuals. 3, 21, 23, 25 PFP may be unique in each of these groups based purely on developmental status. Specifically, open physes, incongruent increases in limb mass relative to limb length, hormonal fluctuations, and underdeveloped neuromuscular control patterns likely expose adolescents to various pathologies and injuries that are not typically seen in adult patients with PFP.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the majority of studies evaluating the epidemiology or risk factors for PFP in this population include pubescent, post-pubescent, and even pre-pubescent individuals. 3, 21, 23, 25 PFP may be unique in each of these groups based purely on developmental status. Specifically, open physes, incongruent increases in limb mass relative to limb length, hormonal fluctuations, and underdeveloped neuromuscular control patterns likely expose adolescents to various pathologies and injuries that are not typically seen in adult patients with PFP.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the proportion of acute versus overuse injuries in youth is approximately 50:50; however, it is feared that the number of overuse injuries is rising ( 12). Conditions such as patellofemoral pain ( 65,87), Osgood-Schlatter disease (41), calcaneal apophysitis (96), little league elbow ( 5 2 ) and little league shoulder ( 114), spondylolysis (53), and osteochondritis dissecans ( 101) are all common overuse injuries seen in children and adolescents subject to repetitive sports training. As youth engage earlier in formal-ized sport and specialize in sport(s) at younger ages, they may be at increased risk of experiencing overuse injury ( 45).…”
Section: Problem 3: Early Sport Specializationmentioning
confidence: 99%
“…A severe lateral subluxation of the patella at active terminal extension of the knee is called the J-sign [1,2] or J-tracking [3]. It is a straight forward clinical sign, sometimes shortly referred to as "dislocation in extension" [4].…”
Section: Introductionmentioning
confidence: 99%